PENGARUH PEMBELAJARAN WIRAUSAHA BERBASIS MASALAH SEBAGAI PEMODERASI TERHADAP MINAT BERWIRAUSAHA MAHASISWA - Christanti, Paramita Lea; Sri Nugroho, Arif Julianto; Prasetyo, Jarot; Uningowati, Dwi Wahyuni; Santoso, Imam (Surakarta Management Journal, 2023)
This research aimed to test whether the learning model obtained by entrepreneurship problem-based can strengthen attitude variables, subjective norms and self-efficacy control of Unwidha undergraduate students' entrepreneurship interest. The research design was carried out using quantitative methods that explained the causal relationship between one variable and the other variables to be tested. The hypothesis test was formulated in a model using the Structural Equation Model multivariate test. The population in this research are all Unwidha undergraduate students who have a strong interest in entrepreneurship. The sampling technique was carried out by purposive sampling of 120 student respondents. The results of the analysis found that entrepreneurship problem-based as a moderator influences student entrepreneurship motivation and the overall model in the SEM fit test. The research results can serve as a basis for making quality entrepreneurial learning problem-based models by adding aspects of real entrepreneurial practice for Unwidha undergraduate students.